Discovery of the Graves of Polish Defenders of the Military Transit Depot on Westerplatte - Dziewanowski, Adam; Kalka, Piotr; Kuczma, Filip (Social consequences of war, 2024)
In 2019, an archaeological team of the Museum of the Second World War in Gdańsk began a scientific program aimed at locating the burial place of Polish soldiers killed during the seven-day defence of the Military Transit Depot at Westerplatte in 1939. A thorough analysis of all available archival sources (witness accounts, archival photographs, results of geophysical surveys, etc.) made it possible to select the area of excavation work where the remains of the fallen were expected to be located. The work, which began in September 2019, confirmed the validity of the initial assumptions and resulted in the discovery of the remains of the Polish defenders of Westerplatte.During the work, a total of five grave cavities were found, containing the remains of nine people. Four skeletons layed in single graves, while five more were in a mass grave. Damages (injuries, cracks, traces of the impact of the shock wave and high temperature) were visible on the uncovered remains, the nature of which indicated that some of the found soldiers were killed in the guardhouse No. 5, a Polish defenders building destroyed by the German Luftwaffe on September 2, 1939. Numerous elements of Polish-made soldier uniforms and equipment, as well as personal items from the period of the Second Polish Republic, were found next to the uncovered remains.Thanks to the cooperation of three institutions: The Museum of the Second World War in Gdańsk, the Institute of National Remembrance and the Pomeranian Medical University in Szczecin, which enabled a multi-track analysis of all available sources: archival, archaeological, anthropological, as well as genetic, seven of the nine discovered defenders of Westerplatte have been fully identified to date. The remains of all the soldiers found, as well as their commander Henryk Sucharski, were laid to rest at the new Polish Army Cemetery at Westerplatte on November 4, 2022 after a solemn state funeral.